PENGEMBANGAN SOAL TES KEMAMPUAN BERPIKIR KRITIS DALAM PELAJARAN IPA KELAS V SEKOLAH DASAR - Sri Desi Yusnita; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the low ability of students in solving critical thinking ability test questions. This is due to the lack of evaluation tools in the form of test questions based on critical thinking skills in the teaching and learning process in elementary schools. Developing test questions based on critical thinking skills in science lessons is expected to improve students' higher-order thinking skills, especially in analyzing a problem, so that it can encourage students to develop their thinking skills. Based on this, critical thinking skills test questions were developed in science lessons for fifth grade elementary school students. The aim of this research is to develop a valid and reliable test of students' critical thinking skills in science lessons for grade 5 elementary school students. The type of research used is research development (Research ang Development). The development model used is a 4-D model consisting of the stages of defining, designing, developing, and disseminating. The test questions developed were validated by 2 material experts and 1 linguist. Data was collected by means of tests and questionnaires. The data that has been collected was then analyzed using ANATES V4 software with 20 5th grade elementary school students as respondents. The validation results show the level of material validity is 78.59% in the very valid category and the level of language validity is 80% in the very valid category. The analysis using ANATES V4 software for the reliability value of 0.81 with a very good category. The discriminatory test results obtained 14 very good questions, 4 good questions and 2 questions with sufficient discriminating power. Analysis of the level of difficulty obtained the results of 5 questions with a difficulty index of difficulty and 15 questions with a moderate difficulty index. Furthermore, the distractor quality test was carried out on the questions, with good results that each alternative answer could be the student's choice when answering the questions.Key Words: Test Questions, Critical Thinking Skills